Acute Hemiballismus Due to Vascular or Diabetic Striatopathy: A Rare Case Report from KHZ Musthafa General Hospital, Tasikmalaya - Nasyifa Nurul; Billy Muchamad Ramdani; Indra Gunawan Affandi (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Hemiballismus is a hyperkinetic movement disorder characterized by sudden, involuntary, high-amplitude ballistic movements of the arm and leg on one side of the body, often due to contralateral central nervous system dysfunction. The most common causes are ischemic stroke and hyperosmolar hyperglycemic syndrome. Stroke-related movement disorders are rare, with an incidence of 0.4%–0.54%, while the prevalence of hyperglycemia-induced, known as diabetic striatopathy (DS), affects approximately 1 in 100,000 individuals, predominantly older women. Case: A 63-year-old male presented with sudden, involuntary left arm movements for one week, starting with throwing-like motions, followed by stiffness, tremors, rapid arm drop, and facial grimacing on the left side. The condition was accompanied by left leg weakness. He had a history of uncontrolled type 2 diabetes mellitus. Physical examination showed left hemiballismus with motor strength 5/5/3/2 and a positive Babinski reflex on the left. Blood tests revealed a random glucose of 686 mg/dL, HbA1C of 15%, and 126 mmol/L sodium. A non-contrast CT scan showed multiple bilateral lacunar infarcts in the basal ganglia region. Discussion: Hemiballismus occurs sporadically and is caused by multiple bilateral lacunar infarcts in the basal ganglia, with risk factors including type 2 diabetes mellitus and advanced age. Other causes, such as stroke and genetic factors, may still be considered. Conclusion: Hemiballismus is a rare form of movement disorder. Vascular and metabolic disorders are the most common causes of hemiballismus. In this case, acute hemiballismus occurred in an elderly stroke patient with type 2 diabetes mellitus as a risk factor.